Peran Guru dalam Membentuk Karakter Peserta Didik pada Siswa Kelas III MI Al-Irsyad Kota Tangerang - Magdalena, Ina; Nurcahyati, Aan; Sakina, Syera Putri; Azahra, Azma; Rohmadona, Adelia; Nabila, Putri; Anggraeni, Rika (Lembaga Yasin AlSys, 2023)
This article aims to look at the role of teachers in shaping the character of students in public elementary schools. This study uses a qualitative approach with data collection techniques of observation, interviews and documentation. The data validity analysis techniques used were triangulation, observation extension and increased persistence. The results of this study found that the teacher's role is very strategic in shaping the character of students because the teacher is not only a person who teaches character values to students theoretically but the teacher also provides an example, so that it is relevant between what is conveyed and what is done by the teacher.. So that it has a very positive impact on the formation of the character of students.